Diversion in the Juvenile Justice System at Kupang Class 1A District Court, Indonesia - Haning, Semuel (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study aims to analyze the implementation of diversion in the juvenile justice system at Kupang Class 1A District Court. Diversion, as an effort to shift criminal proceedings towards a restorative justice approach, is intended to protect children in conflict with the law (ABH). This research employs an empirical juridical method, examining the legal foundations of diversion based on Law No. 11 of 2012 and Perma No. 4 of 2014, while also analyzing diversion practices through interviews with judges, prosecutors, defense attorneys, and social workers. The findings indicate that the implementation of diversion at Kupang Class 1A District Court still faces several obstacles, including limited human resources, resistance from victims, and inadequate supporting facilities. This study recommends enhancing mediator capacity, expanding public awareness of diversion, and improving infrastructure to support a more effective and equitable diversion process.